2011
DOI: 10.1002/hbm.21412
|View full text |Cite
|
Sign up to set email alerts
|

Association between white matter microstructure, executive functions, and processing speed in older adults: The impact of vascular health

Abstract: Cerebral white matter damage is a commonly reported consequence of healthy aging, but is also associated with cognitive decline and dementia. The aetiology of this damage is unclear, however, individuals with hypertension have a greater burden of white matter signal abnormalities (WMSA) on MR imaging than those without hypertension. It is therefore possible that elevated blood pressure (BP) impacts white matter tissue structure which in turn has a negative impact on cognition. However, little information exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
82
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 124 publications
(206 reference statements)
15
82
1
Order By: Relevance
“…Also, consistent with the literature, we found evidence for modest phenotypic correlations between neurocognitive and white-matter integrity, particularly for tests of speed of processing (27,38,39), working and declarative memory (12,13), and IQ (14,25). However, our findings extend this work by Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Also, consistent with the literature, we found evidence for modest phenotypic correlations between neurocognitive and white-matter integrity, particularly for tests of speed of processing (27,38,39), working and declarative memory (12,13), and IQ (14,25). However, our findings extend this work by Fig.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that hypertension has widespread effects on brain white matter. Prior findings that alterations in white matter diffusion metrics are associated with decreased cognitive performance suggest that these changes are not benign 7,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have shown that age-related differences in behavioral and motor task performance are mediated by age-related variations in DWM DTI metrics (Bucur et al, 2008;Hedden et al, 2014;Holtrop et al, 2014;Jacobs et al, 2013;Kerchner et al, 2012;Madden et al, 2009). Nevertheless, in several recent studies, the relationships between DWM diffusion metrics and cognitive ability is attenuated or completely lost after accounting for the effects of age (Bennett et al, 2014;Borghesani et al, 2013;Koch et al, 2013;Lockhart et al, 2012;Metzler-Baddeley et al, 2011;Salami et al, 2012).…”
Section: Discussionmentioning
confidence: 99%